Analisis Kebijakan Versi William Dunn dalam Pondok Pesantren Modern - Nurul Fika; Anis Fauzi; Ahmad Qurtubi (Journal on Education, 2023)
This research uses qualitative research methods with a type of approach, namely library research or literature studies by exploring information through literature related to William Dunn's version of wisdom in modern Islamic boarding schools to answer the focus of the study on this research. This study examines the definition of education policy analysis, forms of public policy analysis, Dunn's version of the policy analysis theory model, the application of William Dunn's policies in pesantren. Policy is one of the most important things that everyone must have in making decisions. Policy can affect something in determining an action. William Dunn's version of policies includes: 1) problem formulation. 2) forecasting the future of the policy. 3) policy recommendations. 4) determination of policy outcomes 5) evaluation of policy performance